Co-designing a peer support programme for carers of people treated under the Mental Health Act: views from stakeholders - Imogen Wells; Kelly Wintsch; Abigail G-Medhin; Brynmor Lloyd-Evans; Steve Gillard; Rose McCabe; Mohamed Yaasir Mohamudbucus; Candelaria Mahlke; Katharina Nagel; Zhenreenah Muhxinga; Swaran Singh; Stefan Priebe; et al. (BMC Psychiatry)
Abstract Background Relatives/friends (carers) of people who are involuntarily admitted to a psychiatric hospital report high levels of stress, feelings of isolation and exclusion from their patient’s care. One-to-one peer support is widely implemented for patients, facilitating mental health recovery. Preliminary evidence reports that peer support may benefit carers too, but a one-to-one peer support programme to help carers when their relatives/friends are in hospital has not been developed. Objective To explore carers’, patients’, and professionals’ views on what an accessible, feasible and helpful one-to-one peer support intervention should consider for carers of patients treated under the Mental Health Act (MHA) in England. Method Nineteen one-to-one interviews were conducted online with five carers, four patients, four clinicians, four independent mental health advocates and two behaviour change experts. Participants had experience of either being treated or supporting someone treated under the MHA within the last 10 years. Audio recordings of the interviews were transcribed, and data were analysed using thematic analysis. Results Five themes were identified: (a) carer availability and awareness; (b) peer support flexibility; (c) early promotion of peer support; (d) appropriate training and support for peers, and; (e) anticipated impact of peer support. Carers’ lack of time and awareness of support were reported as key barriers to accessing peer support. To address this, participants emphasised the need for early introduction of support following patients’ hospitalisation and flexible delivery through various communication channels. They also highlighted the need for robust, interactive training for peer supporters. Expected benefits included improved carer and peer supporter wellbeing and increased carer knowledge and empowerment. Conclusions These findings highlight the need for structured training for peer supporters and a flexible, accessible peer support programme for carers. The findings can inform evidence-based co-production of a carer peer support programme for use in England, which could improve carer wellbeing, knowledge and empowerment.